ANALISIS PENGELOLAAN HUTANG PADA PT. SABA SAGARMATHA DI SAMARINDA - Heriyanto, Karina Sri Fatonah Titin Ruliana 2 (EKONOMIA, 2021)
The purpose of this study was to determine  analyze the increase in  assets of PT. Saba Sagarmatha which was financed by debt in 2017, 2018 and 2019. Financial management is a process in corporate financial activities how to obtain funds, use funds, and manage assets optimally which are used to finance all activities carried out by the company so that it can achieve company goals. This study uses an analytical tool that is measured by the solvency ratio with the type of Debt to Asset Ratio (Debt to Asset Ratio).From the analysis and discussion results indicate that there is a decrease in the assets of PT. Saba Sagarmatha which was financed by debt in 2017, 2018, and 2019 as measured by the Debt to Aseset Ratio (Debt to Asset Ratio). 2017 has a value of 20,59% which mean that 79,41% company assets are financed by other components of capital such as retained capital, 2018 has a value of 14,97% which mean that 85,03% company assets are financed by other components of capital such as retained capital, and 2019 it has a value of 13,68% which mean that 86,32% company assets are financed by other components of capital such as retained capital. This shows that PT. Saba Sagarmatha has a small ratio value, which means that the few assets are financed by debt, or in other words, most assets are financed using equity.Based on the research results, it can be concluded that the hypothesis which states that there is an increase in the assets of PT. Saba Sagarmatha financed by debt in 2017-2019 has increased, rejected.